Novel drugs that target the estrogen-related receptor alpha: their therapeutic potential in breast cancer - May FEB (Cancer Management and Research, 2014)
Felicity EB MayNorthern Institute for Cancer Research and Department of Pathology, Faculty of Medical Sciences, University of Newcastle upon Tyne, Newcastle upon Tyne, UKAbstract: The incidence of breast cancer continues to rise: 1.7 million women were diagnosed with and 521,000 women died from breast cancer in 2012. This review considers first current treatment options: surgery; radiotherapy; and systemic endocrine, anti-biological, and cytotoxic therapies. Clinical management includes prevention, early detection by screening, treatment with curative intent, management of chronic disease, and palliative control of advanced breast cancer. Next, the potential of novel drugs that target DNA repair, growth factor dependence, intracellular and intercellular signal transduction, and cell cycle are considered. Estrogen-related receptor alpha has attracted attention as a therapeutic target in triple-negative breast cancers with de novo resistance to, and in breast cancers with acquired resistance to, endocrine therapies such as antiestrogens and aromatase inhibitors. Estrogen-related receptor alpha is an orphan receptor and transcription factor. Its activity is regulated by coregulator proteins and posttranslational modification. It is an energy sensor that controls adaptation to energy demand and may facilitate glycolytic metabolism and mitochondrial oxidative respiration in breast cancer cells. Estrogen-related receptor alpha increases breast cancer cell migration, proliferation, and tumor development. It is expressed at high levels in estrogen receptor-negative tumors, and is proposed to activate estrogen-responsive genes in endocrine-resistant tumors. The structures and functions of the ligand-binding domains of estrogen receptor alpha and estrogen-related receptor alpha, their ability to bind estrogens, phytoestrogens, and synthetic ligands, and the effects of ligand agonists, antagonists, and inverse agonists on biological activity, are evaluated. Synthetic ligands of estrogen-related receptor alpha have activity in preclinical models of metabolic disorders, diabetes, osteoporosis, and oncology. The clinical settings in which these novel drugs might have utility in the management of advanced breast cancer, and biomarkers for stratification of patients likely to benefit, are discussed. Finally, the potential side effects of the novel drugs on metabolism, osteoporosis, osteo-metastasis, and cachexia are considered.Keywords: estrogen receptor alpha, inverse or reverse agonist, coactivators, ligand-binding domain, TFF1, HER2, antiestrogen-resistance